2005
DOI: 10.1074/jbc.m502922200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sphingosine Kinase 2 in Cell Migration toward Epidermal Growth Factor

Abstract: Sphingosine 1-phosphate (S1P), produced by two sphingosine kinase isoenzymes, denoted SphK1 and SphK2, is the ligand for a family of five specific G protein-coupled receptors that regulate cytoskeletal rearrangements and cell motility. Whereas many growth factors stimulate SphK1, much less is known of the regulation of SphK2. Here we report that epidermal growth factor (EGF) stimulated SphK2 in HEK 293 cells. This is the first example of an agonist-dependent regulation of SphK2. Chemotaxis of HEK 293 cells tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
167
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(186 citation statements)
references
References 54 publications
17
167
1
1
Order By: Relevance
“…Single point mutation of the second conserved glycine residue of the ATP-binding sequence of both SphKs resulted in a complete loss of sphingosine phosphorylating activity (11,35,36). The catalytically inactive G82D-SphK1 and G231E-SphK2 mutants have been shown to block various functions of these enzymes (11,26,36). Expression of G82D-SphK1 or G231E-SphK2 did not significantly affect the increased ceramide levels induced by sphingosine in SPP-1-expressing cells (Fig.…”
Section: Effect Of Spp-1 On Ceramide Metabolism-there Was An Increasementioning
confidence: 99%
See 1 more Smart Citation
“…Single point mutation of the second conserved glycine residue of the ATP-binding sequence of both SphKs resulted in a complete loss of sphingosine phosphorylating activity (11,35,36). The catalytically inactive G82D-SphK1 and G231E-SphK2 mutants have been shown to block various functions of these enzymes (11,26,36). Expression of G82D-SphK1 or G231E-SphK2 did not significantly affect the increased ceramide levels induced by sphingosine in SPP-1-expressing cells (Fig.…”
Section: Effect Of Spp-1 On Ceramide Metabolism-there Was An Increasementioning
confidence: 99%
“…siRNA Transfection-Cells were transfected with 50 nmol of sequence-specific, ON-TARGETplus SMARTpool siRNA against SPP-1 SphK2, and control siRNA from Dharmacon (Lafayette, CO) using Oligofectamine (Invitrogen) as described previously (26). Total RNA was isolated with TRIzol reagent (Invitrogen) and reverse-transcribed with Superscript II (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…15 In addition, ON-TARGETplus SMARTpool siRNA against SphK1, SphK2, and control siRNA from Dharmacon (Lafayette, CO) was used to confirm lack of off-target effects. LAD2 cells were transfected with 100 nM sequencespecific ON-TARGETplus SMARTpool siRNAs against SphK1, SphK2, and control siRNA in Stem-Pro-34 medium using Lipofectamine 2000 (Invitrogen).…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…Increased S1P formation, in turn, activates S1P receptors on the same and͞or neighboring cells in an autocrine or paracrine manner. It has been demonstrated that this type of ''inside-out'' signaling by S1P is critical for migratory responses of fibroblasts and smooth muscle cells toward PDGF (9,12) and human breast cancer cells toward EGF (8). Similarly, S1P secreted by mast cells is important for migration of mast cells toward antigen (Ag) and might be involved in the movement of mast cells to sites of inf lammation (13).…”
mentioning
confidence: 99%
“…1 and 6). To date, only EGF (8) and cross-linking of Ig receptors (4) have been shown to stimulate SphK2.…”
mentioning
confidence: 99%